Nutrition research in rural communities: application of ethical principles - Faber, Mieke (Matern Child Nutr, 2012)
This narrative review focuses on ethics related to nutrition‐specific community‐based research, within the framework of science for society, and focusing on the rights and well‐being of fieldworkers and research participants. In addition to generally accepted conditions of scientific validity, such as adequate sample size, unbiased measurement outcome and suitable study population, research needs to be appropriate and feasible within the local context. Communities' suspicions about research can be overcome through community participation and clear dialogue. Recruitment of fieldworkers and research participants should be transparent and guided by project‐specific selection criteria. Fieldworkers need to be adequately trained, their daily schedules and remuneration must be realistic, and their inputs to the study must be recognized. Fieldworkers may be negatively affected emotionally, financially and physically. Benefits to research participants may include physical and psychological benefits, minimal economic benefit, and health education; while risks may be of a physical, psychological, social, or economic nature. Targeting individuals in high‐risk groups may result in social stigmatization. The time burden to the research participant can be minimized by careful attention to study procedures and questionnaire design. Potential benefits to the community, fieldworkers and research participants and anticipated knowledge to be gained should outweigh and justify the potential risks. Researchers should have an exit strategy for study participants. For effective dissemination of results to individual research participants, the host community and nutrition community, the language, format and level of presentation need to be appropriate for the target audience.